EVALUATION OF PHARYNGEAL AIRWAY DIMENSIONAL CHANGES FOLLOWING ISOLATED MANDIBULAR SETBACK AND BIMAXILLARY SURGERY IN SKELETAL CLASS III PATIENTS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate pharyngeal airway changes after isolated mandibular setback and bimaxillary surgery in patients with skeletal Class III malocclusion.Methods: This retrospective study included 32 patients with skeletal Class III malocclusion, comprising 13 patients who underwent isolated mandibular setback and 19 patients who underwent bimaxillary surgery. Lateral cephalograms were collected at T0 before surgery, T1 immediately after surgery, and T2 at 6 months after surgery. Skeletal displacement was assessed using the coordinates of points A, B, and Pogonion on the horizontal axis (X) and vertical axis (Y). Pharyngeal airway dimensions were measured using VAL, Pm-UPW, U-MPW, V-LPW, PAS-p, and PAS-t.Results: The bimaxillary surgery group had a significantly greater mandibular setback than the isolated mandibular setback group, as shown by point B displacement (-8.14 mm vs. -6.33 mm; p = 0.032). In the isolated mandibular setback group, U-MPW, PAS-p, and PAS-t decreased significantly (p < 0.001). In the bimaxillary surgery group, U-MPW and PAS-p were preserved (p > 0.05), while PAS-t decreased slightly (p = 0.03). Horizontal displacement of point B showed a strong correlation with PAS-t (r = 0.789; p < 0.001) and U-MPW (r = 0.781; p < 0.001).Conclusion: In this selected cohort, isolated mandibular setback was accompanied by reductions in PAS-p and PAS-t at 6 months, whereas the bimaxillary group showed smaller reductions in some airway dimensions. Given the retrospective, indication-based group allocation and the absence of functional respiratory outcomes, these findings indicate an association between horizontal mandibular setback and airway dimensional change but do not support prioritizing one surgical approach.
Keywords: pharyngeal airway; skeletal Class III; BSSO; mandibular setback; bimaxillary surgery; lateral cephalometry.